Neuromodulators signal through astrocytes to alter neural circuit activity and behaviour. - Ma, Z.; Stork, T.; Bergles, D.E.; Freeman, M.R. (Nature, 2016)
Astrocytes associate with synapses throughout the brain and express receptors for neurotransmitters that can increase intracellular calcium (Ca(2+)). Astrocytic Ca(2+) signalling has been proposed to modulate neural circuit activity, but the pathways that regulate these events are poorly defined and in vivo evidence linking changes in astrocyte Ca(2+) levels to alterations in neurotransmission or behaviour is limited. Here we show that Drosophila astrocytes exhibit activity-regulated Ca(2+) signalling in vivo. Tyramine and octopamine released from neurons expressing tyrosine decarboxylase 2 (Tdc2) signal directly to astrocytes to stimulate Ca(2+) increases through the octopamine/tyramine receptor (Oct-TyrR) and the transient receptor potential (TRP) channel Water witch (Wtrw), and astrocytes in turn modulate downstream dopaminergic neurons. Application of tyramine or octopamine to live preparations silenced dopaminergic neurons and this inhibition required astrocytic Oct-TyrR and Wtrw. Increasing astrocyte Ca(2+) signalling was sufficient to silence dopaminergic neuron activity, which was mediated by astrocyte endocytic function and adenosine receptors. Selective disruption of Oct-TyrR or Wtrw expression in astrocytes blocked astrocytic Ca(2+) signalling and profoundly altered olfactory-driven chemotaxis and touch-induced startle responses. Our work identifies Oct-TyrR and Wtrw as key components of the astrocytic Ca(2+) signalling machinery, provides direct evidence that octopamine- and tyramine-based neuromodulation can be mediated by astrocytes, and demonstrates that astrocytes are essential for multiple sensory-driven behaviours in Drosophila.